Legalization Of Islamic Principles (An Analytical Study Of The Maqashidi Interpretation Approach In The Book At-Tahrir Wa At-Tanwir By Thahir Ibn 'Asyur) - Anjaludin, Anjaludin; Zen, Abdul Muhaimin; Ulhaq, M. Ziyad (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The Qur'anic Maqasid in the verses that are almost formal in formalising Islamic Shari'a are as follows: Al-Baqarah/2: 208 emphasising the importance of entering the religion of Islam with its universal values that apply to all human beings. Al-Ma'idah/4:60 explains that taghut is a being other than Allah that is worshipped, and that it is important to obey the legitimate leader. Al-Ma'idah/5:44 gives the definition of disbelief as the disobedience of religious believers to the laws of the heavenly religions, while providing benefits to all humanity. Al-Ma'idah/5:45 and 47 indicate that zalim and fasik are terms for followers of any religion who do not follow the legal provisions of their holy book and do not provide benefits. An-Nisa/4:59 explains that ulil amri are leaders who are just, trustworthy and beneficial. Finally, An-Nisa/4:65 states that Muhammad's shari'a is a just Islamic shari'a and ijtihad law based on justice. All these verses represent the moral ideal of the Qur'an, which aims to fulfil the benefit of mankind and emphasises that the Qur'an is a relevant revelation for all time and place.